(untitled) (UNIZIK Journal of STM Education, 2025)
This study examined the relationship between self-regulation skills and academic achievement of secondary school students in Physics in Awka Education Zone of Anambra State. The study was guided by tworesearch questions and two null hypotheses were tested at 0.05 level of significance. The study adopted a correlation research design. The population of the study consisted of 2532 secondary school two (SS 2) students offering Physics from all the public secondary schools in the zone. Multi-stage sampling procedure was used to draw 345 secondary school two (SS 2) students from the population. The instruments used for data collection included; Physics Self Regulation Questionnaire (PSRQ) and average scores of students for 2024/2025 academic session. The instruments PSRQ was validated by three experts, two from the Department of Science Education and one from Department of Educational Foundations (Measurement and Evaluation unit), all in Nnamdi Azikiwe University, Awka. The reliability of the instrument was established using Cronbach’s alpha method, with coefficient of 0.86 for PSRQ, indicating satisfactory internal consistency. Data collection was done through direct administration of the questionnaire to respondents by the researcher and research assistants who are secondary school Physics teachers. Pearson product moment correlation was employed for the analysis of the data collected using Statistical Package for Social Sciences (SPSS, vs 27). The findings of the study revealed that there is a moderate positive and significant relationship between self-regulation skills scores and academic achievement scores of secondary school students in Physics. In addition, the study showed that there is moderate positive and significant relationship between self-regulation skills scores and academic achievement scores for both male and female secondary school students in Physics in Awka Education Zone. Based on the findings, the study concluded that self-regulation skills play a crucial role in enhancing students’ academic achievement in Physics. It was recommended amongst others that Physics teachers should deliberately incorporate strategies such as goal setting, self-planning, self-monitoring, and self-reflection into classroom activities to strengthen students’ self-regulation skills, which have been shown to significantly enhance academic achievement.